A marine chemical ecology study of the sea hare, Bursatella leachii in South Africa,Marine chemical ecology study of a South African sea hare Bursatella leachii - D'Souza, Nicole (Rhodes University, Faculty of Science, Department of Chemistry, 2013)
The large cosmopolitan sea hare Bursatella leachii is a common resident in Eastern Cape river mouths during summer and late autumn where they congregate in beds of Zostera capensis to breed. In this thesis, the previously known toxic formamide marine secondary metabolite (-)-bursatellin (2.2), which may deter predators of South African specimens of the globally distributed sea hare Bursatella leachii, was isolated and identified (Chapter 2). There have been no previous chemical ecology studies of B. leachii and the latter half of this thesis is devoted to chemical ecology studies of this organism. Interestingly, the isolation of the (-)-diastereomer of 2.2 from specimens of B. leachii collected from the Kariega River mouth (near Kenton-on-Sea) suggests that the South African specimens of this species are similar to specimens collected from Puerto Rico and from the Mediterranean Sea. Two different chromatographic techniques for isolating 2.2 were compared in order to maximize the amount of 2.2 isolated from the Kariega River mouth sea hares. The doubling of selected resonances observed in both the ¹H and ¹³C NMR spectra of the bursatellin isolated in this study suggest one of three possibilities; either firstly, the presence of closely related compound(s), secondly, the presence of diastereomers or thirdly the presence of rotamers. Through NMR kinetic studies, we were able to establish that the presence of rotamers was very unlikely due to no change in the relative ratio (3:1) of the ¹H NMR signals with an increase in temperature. Although the attempted synthesis of the acetate derivative (2.28), as a means of separating a diastereomeric mixture was successful, the chromatographic separation of the proposed acetylated diastereomers was not successful. Preparation of the camphanate ester derivatives (e.g. 2.30) proved to be unsuccessful. Five B. leachii specimens were dissected, their organs separated and individually extracted with methanol. The methanol extracts were individually chromatographed on HP-20 media, and the distribution of bursatellin determined by isolation and NMR. It was evident from this investigation that the distribution of 2.2 within individual B. leachii specimens was found to be highest within the B. leachii ink gland. The lower amounts of 2.2 contained in the digestive system, relative to other organs, was hypothesized to occur because 2.2 is sequestered from the diet of the sea hare and efficiently moved from the gut to various organs around the body where it is stored. The absence of 2.2 from the skin was surprising and may be a result of a smaller mass of skin relative to other organs coupled with the limitations of the chromatographic separation techniques employed. Surprisingly, no bursatellin was found within juvenile sea hares. Chapter three discusses the isolation of ilimaquinone (3.1) and pelorol (3.19) from the sponge Hippospongia metachroma and the structure elucidation of each compound using computer modeling to illustrate the conformation. It was deemed necessary to isolate these well known and abundant bioactive marine natural products from a sponge as standard compounds in the bioassays given the paucity of 2.2 available for this study. Chapter four describes the assays used to test the biological activity of the bursatellin 2.2 compared to the generally bioactive ilimaquinone and the structurally related and commercially available broad spectrum antibiotic chloramphenicol. B. leachii, a shell-less marine mollusc inhabits a variety of intertidal habitats and, therefore, is exposed to several different predators, yet does not appear to have any specific predators. Potential predators of this sea hare in the Kariega Estuary could be fish and amphipods which are found in close proximity to these sea hares. Results of the assays showed that at roughly natural concentrations, (calculated from the isolated chromatographic yield) feeding was deterred by the fish and amphipods, which implied that 2.2 may confer a defensive role within the organism. The relatively high concentration present within the ink gland of B. leachii may support this hypothesis. Surprisingly, given its structural similarity to chloramphenicol, 2.3 did not show any antimicrobial action against five of the six bacterial strains against which it was screened [chloramphenicol inhibited the growth of all the bacterial strains at very low concentrations (0.25 mg/mL)]. Bursatellin was found to be only active against Staphylococus aureus at high concentrations ca. 2 mg/mL when compared to chloramphenicol. Neither bursatellin nor chloramphenicol showed anti-fungal activity. Although this study suggests that the sea hares may use chemical defences in addition to opaline ink to defend themselves, they also live within the seagrass Z. capensis, which possibly provides the sea hare with a cryptic form of physical defence against several predators that are unable to swim freely within the weed beds in the littoral zone of the estuary.,Adobe Acrobat 9.53 Paper Capture Plug-in
Keywords: Sea hares (Mollusks) -- South Africa -- Kenton-on-Sea; Sea hares (Mollusks) -- Ecology -- South Africa -- Kenton-on-Sea; Sea hares (Mollusks) -- Behavior -- South Africa -- Kenton-on-Sea; Sea hares (Mollusks) -- Defenses -- Behavior -- South Africa -- Kenton-on-Sea